The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation. (11th December 2019) - Fan, Jing; Liu, Jie; Gong, Zhi‐You; Xu, Pei‐Zhou; Hu, Xiao‐Hong; Wu, Jin‐Long; Li, Guo‐Bang; Yang, Juan; Wang, Yu‐Qiu; Zhou, Yu‐Feng; Li, Shuang‐Cheng; Wang, Li; et al.
Summary: Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11, SWEET14 and SUT5, and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.